Association of altered thyroid function and prolactin level in polycystic ovarian syndrome (Bangladesh Medical Journal, 2016)
Polycystic ovarian syndrome (PCOS) is a common disorder for female with fertile age. Along with other clinical and biochemical manifestations, thyroid function and prolactin level may be altered in patients with PCOS. This study aimed to evaluate the clinical and biochemical status, as well as alteration of thyroid stimulating hormone (TSH), prolactin (PRL) level in patients with PCOS. Present study comprised of 100 diagnosed PCOS patients according to revised Rotterdem Consensus criteria. All patients were studied for serum testosterone, LH (lutenizing hormone), FSH (follicle stimulating hormone), blood glucose, lipid profile as well as TSH, FT4 (free thyroxin) and prolactin level. Out of 100 PCOS patients 97 had hirsutism, 64 had acanthosis nigricans, where menstrual irregularities were in 94 patients. Diastolic blood pressure (74±1.1 vs. 77±0.9, mmHg; p=0.017), total cholesterol (163±5.3 vs. 193±6.2 mg/dl; p